Validating the instrument to measure entrepreneurial traits - Al Mamun, Abdullah; Yusoff, Mohd Nor Hakimin; Ibrahim, Mohamed Dahlan (2018)
The objective of this study is to develop a distilled measure for entrepreneurial traits particularly in the context of low-income households in Malaysia. In this attempt, the following study examined the need for achievement, locus of control, tolerance of ambiguity, visionary, persistence, and resilience as components to develop an instrument to measure entrepreneurial traits among low-income households in Kelantan, Malaysia. The study adopted a cross-sectional design and collected quantitative data through structured interviews from 800 low-income households across four districts in Kelantan, Malaysia. Based on the reliability and validity tests, this study finalized the instrument reducing a 58 items scale to 20 items yielding four factors, i.e., need for achievement (five items), tolerance of ambiguity (five items), visionary (four items), and persistence (six items). Findings of the reflective hierarchical model revealed that persistence is the highest contributor towards entrepreneurial traits among the low income households in Kelantan, followed by tolerance of ambiguity, need for achievement, and visionary. It is recommended that future researchers further extend the developed measure by cross-examining the instrument forwarded by this study across different income-level groups living throughout diverse economies.